Centralized blood screening results in Ningxia - Fang LI; Qing LIU; Guoqin ZHENG (Zhongguo shuxue zazhi, 2022)
Objective To retrospectively analyze the quality status and annual trend of provincial-level centralized blood screening across Ningxia, and discuss the effect and advantages of the application of centralized blood screening. Methods The centralized detection, with the combination of enzyme linked immunosorbent assay (ELISA) and nucleic acid test(NAT), in Ningxia from 2016 to 2020 was statistically analyzed, and the sample size, overall unqualified rate and unqualified rate of each item were compared among different regions. Results There were about 70 000 samples in Ningxia annually, 65% were in Yinchuan city, and 35% in Shizuishan, Wuzhong, Guyuan and Zhongwei city. The unqualified rates of blood screening in above five cities were 1.09% (2 438/223 852), 1.48% (401/27 024), 1.50% (425/28 364), 1.01% (351/34 772) and 1.45% (435/30 002) respectively. Significant differences were noticed in the unqualified rates of HBsAg, anti-HCV, anti-TP, HIV Ab/Ag, ALT and HBV DNA (P<0.05), but not in HCV RNA and HIV RNA (P>0.05) among the five cities. Conclusion Centralized blood screening at provincial-level in Ningxia can optimize the allocation of laboratory resources and better ensure blood safety, which is of great significance to the construction of urban public health system in Ningxia.